Agile Curriculum Development For Informatics Using Scrum, Notion, And Coda - Indra Surya Permana; Franciskus Antonius Alijoyo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research focuses on the implementation of the SCRUM method in the curriculum renewal process of the Informatics study program at Mahardika Institute of Technology and Health Cirebon, utilizing digital tools Notion and Coda.io. The main objective of this research is to explore how the SCRUM method can enhance efficiency and effectiveness in curriculum development, facilitate team collaboration, and introduce complex database concepts to non-IT faculty through user-friendly applications. The research findings indicate that the implementation of the SCRUM method significantly improves the quality and speed of curriculum development, while Notion and Coda.io facilitate documentation, communication, and team collaboration. This research concludes that integrating the SCRUM method and digital tools provides an effective approach to curriculum renewal in the digital era, ensuring that the curriculum remains relevant to current industry and technological needs. Limitations of the research include focusing on one institution and study program, suggesting the need for further research to validate these findings in a broader context.